Evolution of ZW Sex Chromosomes in Ptyas Snakes (Reptilia, Colubridae): New Insights from a Molecular Cytogenetic Perspective - Setti, Príncia Grejo; Ezaz, Tariq; Deon, Geize Aparecida; Utsunomia, Ricardo [UNESP]; Tanomtong, Alongklod; Ditcharoen, Sukhonthip; Donbundit, Nattasuda; Sumontha, Montri; Seetapan, Kriengkrai; Buasriyot, Phichaya; Pinthong, Krit; Thongnetr, Weera; et al. (MDPI, 2025)
Snakes are cytogenetically dynamic, characterized by largely conserved diploid chromosome numbers although displaying varied variable evolutionary stages of their sex chromosomes. This study examined four snakes, with a special focus on the genus Ptyas, to provide evolutionary insights into the evolution of ZW sex chromosomes. We performed an extensive karyotype characterization using conventional and molecular cytogenetic approaches, described for the first time the karyotype of Ptyas korros, and revisited the karyotype descriptions of P. mucosa, Chrysopelea ornata, and Fowlea flavipunctatus. We found that all species except F. flavipunctatus have highly heterochromatic W chromosomes enriched in satDNAs or microsatellite repeats. Repetitive sequences accumulate with the heterochromatinization of the W chromosome but are not necessarily associated with this process, demonstrating the dynamic makeup of snake sex chromosomes. Autosomal locus-specific and sex chromosome probes from Pogona vitticeps and Varanus acanthurus did not show hybridization signals in Ptyas snakes, suggesting divergent evolutionary pathways. This finding highlighted the dynamic nature of sex chromosome evolution in snakes, which occurred independently in lizards.